THE POWER OF THE SANAD NETWORK AND ISLAMIC DISCOURSE IN THE ARBA'IN HADITH MANUSCRIPTS OF NUSANTARA SCHOLARS - Muhammad Rikza Muqtada; Arif Friyadi; Mochamad Tholib Khoiril Waro; Abdullah Hanapi (Riwayah: Jurnal Studi Hadis, 2022)
Islam Nusantara was introduced as a response to the issue of radicalism and terrorism that was emerging on the international stage. The pesantren-style education model, which focuses entirely on studying the kitab kuning (turats), is considered effective in addressing this issue. The kitab kuning serves as an effective medium for promoting religious moderation within the socio-cultural context of Muslims in the Nusantara. One approach is by exploring the manuscript heritage written by Nusantara scholars. This paper examines Arba’in hadith manuscripts written by Nusantara scholars, namely the works of Mahfuzh al-Tarmasi, Hasyim Asy’ari, Nawawi al-Bantani, and Yasin al-Fadani, from the 17th to the 20th century. Using a philological approach, the findings of this study show that these books were written in the context of Indonesia’s colonial period and aimed to provide a counter-narrative to religious orthodoxy. The Islamic discourse embedded in these works relates to: 1) Morality, which encourages a moderate attitude towards everyone, all creatures on earth, even towards enemies; 2) Religious moderation, by considering those of different faiths as brothers; 3) Work discipline, aimed at fostering the spirit of striving for a decent life; 4) The concepts of sunnah and bid’ah are explained to provide a counter-narrative to the Wahhabi-style religious discourse that attacks local traditions. Furthermore, at roughly the same time, Muslims in Haramain took a stricter stance toward tradition and sought to return religion solely to the Qur'an and Hadith, while Muslims in the Nusantara were more receptive to local traditions. This is evidenced by the incorporation of local contexts into Arba’in hadith works, such as the emphasis on mutual compassion in the context of Dutch colonialism. This represents the scholarly independence of hadith studies developed by Nusantara hadith scholars.